The Effectiveness of Duolingo Application in Enhancing Efl Student’s Pronunciation: Voiced and Voiceless Consonants - Nalole, Debby Oktaviani Merajiwati; Karmila Machmud; Fahria Malaba (Politeknik Kebangsaan, 2025)
This study aimed to evaluate the effectiveness of the Duolingo application in improving students' pronunciation skills, with a specific focus on voiced and voiceless consonants. A quantitative study design employing a pre-experimental approach was utilized, incorporating pre-tests and post-tests to measure differences in students' scores. The study involved 32 eighth-grade students from SMP Negeri 12 Gorontalo. The students participated in four pronunciation training sessions using the Duolingo application, supplemented with in-class guidance. The collected data were analyzed using a paired t-test to determine the significance of differences between pre-test and post-test scores. The results indicate that the null hypothesis (H₀) was rejected, signifying a significant difference between pre-test and post-test scores. These findings suggest that the Duolingo application significantly enhances students’ pronunciation skills, particularly in mastering voiced and voiceless consonants. Consequently, Duolingo proves to be an effective learning tool for improving students’ pronunciation proficiency.